Diagnóstico del Síndrome de Cushing mediante la determinación de cortisol en sangre y saliva. - Chinche Adriano, Yesenia Maribel (2022)
The present research work is about “CUSHING'S SYNDROME” is a disease caused by the increase in the hormone cortisol in the body, secreted by the adrenal glands, which affects most body tissues, people with this syndrome tend to develop different symptoms such as facies round face, buffalo hump, stretch marks and central obesity, what drives hunger side effects, such as high blood pressure, diabetes and glucose intolerance. The aim of this research is to analyze the clinical usefulness of the production of cortisol in blood and saliva, through the review of scientific information, for Cushing's Syndrome. The study was a descriptive nature with a cross-sectional cohort documentary design, 56 bibliographies were analyzed, also this kind pathology was researched , the methods of analysis for its study and cortisol reference values in biological fluids that were published since 2012 until this date, the information was collected from the endocrinology textbooks, Scielo, Elsiever, Medigraphic, Pubmed, Redalyc and academic Google, for which the observation technique was used through a quantitative observation guide for the collection and treatment of scientific information. According to the reviewed articles, it is shown that saliva is the most used biological fluid for cortisol quantification and its ready obtainability , considering that the samples were taken at night, which is very efficient for diagnosing Cushing's Syndrome.